Sistem Monitoring Limbah Cair Berbasis Mikrokontroler Dengan Data Logger Di Pabrik Kelapa Sawit - Ilham Ilham; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Temperature, Hydrogen Potential (pH), and Turbidity are important information to know to see the physical elements of liquid waste. This research was conducted using the Arduino Uno Microcontroller as a controller, temperature sensor (DS18B20), pH sensor, Turbidity sensor and SD card module for data logger and real time. The results of namely the pH sensor with an average error of 1.09%, the temperature sensor of 3.05% and the turbidity sensor of 3.46%. For the time of sending data from Arduino Uno to SD card every 30 minutes. the success of a measuring instrument that displays readings on a Liquid Crystal Display (LCD) and recording data stored on a memory card. From the test results to the field, data obtained the average value of the pH sensor voltage reading of 2.89 volts with the average pH value being read by the pH sensor of 5.30, for the average value of temperature sensor readings of 37 °C and for average The average voltage reading on the turbididy sensor is 2.55 volts with an average turbidity level of 296 NTU. Keywords: Arduino Uno Microcontroller, Turbidity Sensor, pH Sensor, Temperature Sensor, and Data Logger